THE INFLUENCE OF FOREIGN DEBT ON ECONOMIC GROWTH IN INDONESIA IN 2013-2022 - Savinca, Bening Aura; Anggraini, Elisa Tri (Jurnal Ilmiah Wahana Pendidikan, 2024)
The objective of this article is to empirically examine the theory on the impact of foreign debt on economic growth in emerging nations, with a particular focus on Indonesia. The author used a panel data regression methodology to examine the relationship between economic growth, serving as the dependent variable, and foreign debt, acting as the independent variable. The data utilized in this study is sourced from the Central Statistics Agency (BPS) and covers the period from 2013 to 2022. The findings of the analysis indicate that there exists a statistically significant and positive relationship between foreign debt and economic development in Indonesia. The coefficient estimate for this relationship is 0.778%. This implies that a 1% rise in foreign debt will result in a corresponding 0.778% increase in economic growth. This shows that foreign debt can be a useful source of development financing for Indonesia, as long as it is managed well and used for productive sectors. This article also provides several policy recommendations related to managing foreign debt in Indonesia, such as increasing transparency, accountability and public participation, optimizing the allocation and efficiency of debt funds, and maintaining a balance between foreign debt and other sources of financing.